The limitations and possiblilites of identity and form in selected recent memoirs and novels by white, female Zimbabwean writers : Alexandra Fuller, Lauren Liebenberg - Eppel, Ruth (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2013)
This study examines selected works by four white female Zimbabwean writers: Alexandra Fuller, Lauren Liebenberg, Bryony Rheam and Lauren St John, in light of the controversy over the spate of white memoirs which followed the violent confiscation of white farms in Zimbabwe from 2000 onwards. The controversy hinges on the notion that white memoir writers exploit the perceived victimhood of white Zimbabweans in the international sphere, and nostalgically recall a time of belonging "“ as children in Rhodesia "“ which fails to address the fraught colonial history which is directly related to the current political climate of the country. I argue that such critiques are too generalised, and I regard the selected texts as primarily critical of the values and lifestyles of white Rhodesians/Zimbabweans. The texts I have selected include a range of autobiographical and fictional writing, or memoirs and pseudo-memoirs, and I focus on form as a medium enabling an exploration of identity. The ways in which these authors conform to and adapt particular narratives of becoming is examined in each chapter, with a particular focus on the transition from innocence to experience, the autobiography, and the Bildungsroman. Gender is a recurring point of interest: in each case the female selves/protagonists are situated in terms of the family, which, in reflecting social values, is a key site of conflict. In regard to trends in white African writing, I explore the white African (farm) childhood memoir and the confessional mode. Ultimately I maintain that while the texts may be classified as white writing, as they are fundamentally concerned with white identity, and therefore evince certain limitations of perspective and form, including clichéd tendencies, all the writers interrogate white identity and the fictional texts more self-reflexively deconstruct tropes of white writing.
Keywords: Women, White -- Zimbabwe -- Biography; Women, White -- Zimbabwe -- Fiction; Zimbabwean fiction (English) -- 21st century; Women, White -- Zimbabwe -- Autobiography; Fuller, Alexandra, 1969-; Liebenberg, Lauren; St. John, Lauren, 1966-; Rheam, Bryony